Structural Determinants of Risky Sexual Practices Among Ship Crew Members in Indonesia: A Qualitative Study - Mustar; Hasnidar; Sulfianti; Khairil Asnan Haedar; Dyan Paramitha Darmayanti (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Ship crews are highly susceptible of HIV infection. Masculinity (most of crews were men), highly mobile (less peer intervention), ease of commercial sexual intercourse, and emotional distress (limited working space and interaction) are the main drivers that tend to exacerbate crew's vulnerability to high-risk sexual behaviors. However, understanding their structural vulnerabilities (in socio-behavioral scope) remain underexplored. This study aims to examine the socioal, cultural, economic, and occupational factors that influence risky sexual behavior among ship crew members (ABK) in Ambon Port. with particular attention to masculinity norms, mobility, transactional sex, and emotional needs. Methods: Qualitative research approach was employed as the analysis basis of the analysis. Data were gathered using semi-structured, in-depth interviews with 25 male ship crews, recruited through snowball sampling. Pre-determined theories (i.e. hegemonic masculinity theory, sexual economy theory, and mobility and health risk frameworks) were utilized as scoping guide to analyze data thematically, focusing on the structural and psychosocial determinants of sexual risk behavior. Results: Lack of knowledge were not a factor to risky sexual behavior as many informants were aware of HIV risks. On the other hand, the behavior apparently embedded in hypermasculine peer cultures (e.g. normalizing promiscuity, stigmatize prophylactic use, and enforce conformity through social ostracism and marginalization. Crew's financial leverage enables them to have commercial sexual intercourse throughout ship's docking at a port. In addition, permissive culture, identity shifting, and emotional distress (e.g. loneliness, absence of peer-led moral control) alleviates as a coping mechanism. Conclusion: To address sexual risk behavior among ship crew members structural occupational health interventions are needed, which target the most well-heared crew to build community peer moral control. Our analysis highlights the importance of educate maritime workers via Port Health Officers, since the behavior done within a port or while the ship's docked. Site-specific interventions at ports should be the first mitigation to prevent risky behavior or at the very least, facilitate moral adherence to 'safety' practices.